2018
DOI: 10.3390/ijerph15051039
|View full text |Cite
|
Sign up to set email alerts
|

Map Changes and Theme Evolution in Work Hours: A Co-Word Analysis

Abstract: (1) Background: Work hours are the basic carrier impacting employees’ work–life experience and organizational performance, and employees have greater anxiety in relation to work hours as new technology requires an increasingly faster work rhythm. However, scientific research on this topic lags far behind the practice, calling to attention the need for research on work hours from the perspective of historical evolution; (2) Methods: The Bibliometric method is used to analyze the 6364 articles and their containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Most research on work hours focused on developed countries such as the United States and Japan, while researches in developing countries were slightly limited. Moreover, numerous studies have shown that the number of work hours in developing countries is higher than that in developed countries (Liu et al, 2018), and the psychological harm caused by long work hours in developing countries was more serious than that in developed countries (Fitzgerald et al, 2015). Especially for the current China, studies have shown that overtime work by Chinese employees ranked among the highest in East Asia (Yamashita et al, 2016), and the issue of job-related time pressure among Chinese workers needs urgent attention.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on work hours focused on developed countries such as the United States and Japan, while researches in developing countries were slightly limited. Moreover, numerous studies have shown that the number of work hours in developing countries is higher than that in developed countries (Liu et al, 2018), and the psychological harm caused by long work hours in developing countries was more serious than that in developed countries (Fitzgerald et al, 2015). Especially for the current China, studies have shown that overtime work by Chinese employees ranked among the highest in East Asia (Yamashita et al, 2016), and the issue of job-related time pressure among Chinese workers needs urgent attention.…”
Section: Introductionmentioning
confidence: 99%
“…At the macro level, the evolution of work hours and the research on its influencing factors were relatively weak, which made it difficult to understand the research status and evolution of work hours, systematically and comprehensively. Moreover, most recent studies on work hours concentrated on developed countries (12), such as some European nations (13), and Japan (14). Studies have rarely been carried out on developing countries, and have failed to explore the influencing factors in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies focused on the effect of work hours on the organization and the individual. Few have sought to understand this issue from a more extensive and comprehensive perspective [11].…”
Section: Introductionmentioning
confidence: 99%